The construction of a new technological innovation system in a follower country: wind energy in Portugal - Bento, Nuno (2015)
This article analyzes the process of construction of a new innovation system based on wind energy in a "follower" context. The technological innovation systems framework is used to analyze and explain the emergence of a new wind industry in Portugal, where this renewable energy technology knew a spectacular development in the past decade. This framework highlights the main processes or functions that intervene in the diffusion of a new technology. The evidence obtained demonstrates that the fulfillment of these functions, which were mostly studied in the context of pioneer countries, is still pertinent to explain the formation of a wind energy system in this follower country. Yet the type of resources and the nature of the activities needed to adopt the technology in the latter will often differ. This case provides new insights about the importance of functions that enhance the follower's capacity to assimilate the new technology (e.g. local knowledge development, experimentation), creating conditions for a fast move as soon as innovations become sufficiently mature in the core.